SPOCK2 controls the proliferation and function of immature pancreatic β-cells through MMP2 - Katarzyna Blaszczyk; Anna P. Jedrzejak; Natalia Ziojla; Ekaterina Shcheglova; Karolina Szarafin; Artur Jankowski; Christine A. Beamish; Jolanta Chmielowiec; Omaima M. Sabek; Ashok Balasubramanyam; Sanjeet Patel; Malgorzata Borowiak (Experimental and Molecular Medicine)
Abstract Human pluripotent stem cell-derived β-cells (SC-β-cells) represent an alternative cell source for transplantation in diabetic patients. Although mitogens could in theory be used to expand β-cells, adult β-cells very rarely replicate. In contrast, newly formed β-cells, including SC-β-cells, display higher proliferative capacity and distinct transcriptional and functional profiles. Through bidirectional expression modulation and single-cell RNA-seq, we identified SPOCK2, an ECM protein, as an inhibitor of immature β-cell proliferation. Human β-cells lacking SPOCK2 presented elevated MMP2 expression and activity, leading to β-integrin-FAK-c-JUN pathway activation. Treatment with the MMP2 protein resulted in pronounced short- and long-term SC-β-cell expansion, significantly increasing glucose-stimulated insulin secretion in vitro and in vivo. These findings suggest that SPOCK2 mediates fetal β-cell proliferation and maturation. In summary, we identified a molecular mechanism that specifically regulates SC-β-cell proliferation and function, highlighting a unique signaling milieu of SC-β-cells with promise for the robust derivation of fully functional cells for transplantation.